Effect of hydrological variability on the biogeochemistry of estuaries across a regional climatic gradient. (15th August 2018) - Montagna, Paul A.; Hu, Xinping; Palmer, Terence A.; Wetz, Michael
Abstract: Given projected changes in river flow to coastal regions worldwide due to climate change and increasing human freshwater demands, it is necessary to determine the role hydrology plays in regulating the biogeochemistry of estuaries. A climatic gradient exists along the Texas coast where freshwater inflow balance ranges from hydrologically positive to negative (where evaporation exceeds inflow) within a narrow latitudinal band, providing a natural experiment for examining inflow effects. Four Texas estuaries ranging from mesosaline to hypersaline were studied for 3 yr to determine how hydrological changes alter the biogeochemistry within and among the estuaries. Trends in dissolved inorganic nutrients, chlorophyll, dissolved organic matter, and carbonate chemistry indicated that these estuaries had drastically different biogeochemical signatures. Nutrients and chlorophyll patterns illustrated an emerging paradigm where phytoplankton biomass in positive estuaries is supported by "new" nitrogen from riverine input, while high concentrations of reduced nitrogen (organic, ammonium) allowed for high chlorophyll in the negative estuary. For carbonate chemistry, a positive estuary receiving river input from a limestone‐dominated watershed was well‐buffered under moderate to high freshwater inflow conditions. When weathering products were diluted during high‐flow conditions, there is carbonate undersaturation (for aragonite) and decreases in pH. However, "acidification" was not observed in the negative estuary because evaporation concentrated the dissolved species and increased buffering capacity. Hydrological changes over spatial gradients are analogous to climatic changes over time, meaning climate change forecasts of higher temperatures and decreased precipitation can make the biogeochemistry of fresher estuaries change to the patterns of saltier estuaries.